Health risk assessment and comparative study on heavy metal levels in indigenous cereal-legume blends (CLBs) on Ghanaian markets - Yaw Doudu Takyi; Jonathan Awewomom; Samuel Selorm Attu; Osei Akoto; Marina Aferiba Tandoh (Cogent Food & Agriculture)
The safety of processed grains and pulses is of health concern so far as heavy metal pollution is concerned. Despite the numerous nutritional benefits sourced from the consumption of cereals and legumes, its heavy metal pollution cannot be overlooked, since it causes adverse health effects. This study sought to measure then compare Cd, Fe, Pb and Ni levels in the various blend classifications, again compare measured levels to heavy metal specifications by regulatory bodies and then determine health risks associated with contamination by these metals. Fifteen samples grouped under three classifications were wet digested using a triacid combination of HNO3, H2SO4 and HClO4, then analysed using an Atomic Absorption Spectrophotometer (AAS). In all samples, levels of heavy metals were detectable. Measured levels ranged from 1.90 to 3.96, 25.74 to 216.78, 0.16 to 0.40 and 0.07 to 0.40 all in mg kg−1 for Cd, Fe, Pb and Ni respectively. EC and China’s maximum limit for Cd was exceeded by all 15 samples. Samples exceeded EC’s maximum limit for Pb, where as 86.67% of samples exceeded that set by China. Consumption of cereal-legume blends contaminated by these heavy metals may pose potential carcinogenic and non-carcinogenic health risks in this study.